The Role of The Movement Teacher in Preparing Indonesia's Excellent Generation - Ulul Azmiyah; Anita Puji Astutik (Program Studi Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2021)
In preparing the fantabulous next generation is not easy, but it is possible with the right education and the existence of teacher movement (Guru Pengerak). Teacher mover will have positive impact in preparing students and the educational institution in the future. The teacher mover in freedom to learn has their duties and functions. The teacher mover must be accustomed to think creatively and innovatively in creating the best ways for students, then learning activities will be fun and creative. The goal in freedom to learn is increasing and improving the education quality in Indonesia through the teacher mover. Considering the teacher mover’s tasks, functions and roles is emphasizing the learning process that focused on students, students are become more innovative, creative and able to develop their potential optimally. This research uses library research. This study describes about the role of teacher mover and the superior generation in the future by defining, analyzing, explaining and understanding the role of teacher mover as an agent who has the positive impact in learning process and creating superior generation in the future.